Economic Growth, International Financial Integration, and Geopolitical Uncertainty: A PVAR Approach Across Developed and Developing Countries - Tarchoun, Monaem (International Journal of Energy Economics and Policy, 2025)
This study investigates the relationship between international financial integration (IFI) and economic growth (GDP) under the influence of geopolitical risk (GPR). Using a balanced panel of 60 countries—classified into developed and developing economies—over the period 1995–2023, the analysis applies a Panel Vector Autoregressive (PVAR) framework to examine the dynamic linkages among GDP, IFI, foreign direct investment (FDI), and GPR. The empirical results reveal that IFI exerts a positive and statistically significant impact on economic growth across both country groups. However, the magnitude of the effect is stronger in developed economies, reflecting their higher institutional quality and more advanced financial systems. In contrast, developing economies are more susceptible to adverse shocks arising from geopolitical tensions, which tend to undermine GDP growth and offset some of the gains associated with financial integration. Impulse response functions and forecast error variance decompositions confirm the presence of bidirectional causality between IFI and economic growth, with notable heterogeneity and non-linearities across income groups. Overall, the findings highlight the importance of institutional quality and risk management frameworks in enabling economies to maximize the growth benefits of financial integration while mitigating their exposure to geopolitical risks.